ANALISIS YURIDIS TERKAIT DENGAN PENILAIAN HAKIM TERHADAP ALAT BUKTI SURAT DALAM PERKARA GUGATAN PEMBATALAN MEREK - Amartha Christine; Gandes Candra Kirana (Reformasi Hukum Trisakti, 2021)
The law of evidence can be said to be the key to whether or not a lawsuit filed according to the Civil Procedure Code is proven, where documentary evidence which is the main evidence plays an important role which must be considered by the panel of judges. The formulation of the problem that the author discusses is how the strength of the documentary evidence provided for in Article 164 of the Herzien Inlandsch Regulation is related to the evidence by the Plaintiff in the Trademark Cancellation Lawsuit? and whether the consideration of the Panel of Judges in the verdict which did not take into account the documentary evidence provided by the party filing the lawsuit complied with the Provisions in the Civil Procedure Code? The research was conducted using normative juridical research methods, using secondary data. Based on the results of the analysis, the Panel of Judges did not consider the documentary evidence in the form of an authentic deed submitted by the Plaintiff.